Malassezia furfur Emergence and Candidemia Trends in a Neonatal Intensive Care Unit During 10 Years: The Experience of Fluconazole Prophylaxis in a Single Hospital - Chen, I-Ting (Adv Neonatal Care, 2020)
BACKGROUND: Because Candida spp is a major cause of mortality and morbidity in preterm infants, fluconazole prophylaxis has been suggested by some experts and hospital policy. In our hospital, fluconazole prophylaxis was used in eligible preterm infants and set as the neonatal intensive care unit (NICU) practice in 2014. PURPOSE: This study focused on fungal bloodstream infections and aimed to evaluate the benefit and harm of fluconazole prophylaxis. METHODS/SEARCH STRATEGY: This retrospective, descriptive study involved medical record reviews in our hospital from April 2005 to October 2016. NICU patients were included if Candida species, yeast-like organisms, or Malassezia species were cultured from their venous catheter tips or blood cultures. FINDINGS/RESULTS: After fluconazole prophylaxis, cases of Candida spp decreased and those of Malassezia furfur emerged. We reviewed 19 cases of catheter-related M furfur colonization and 1 case of M furfur fungemia. The gestational age was 27.3 ± 2.0 weeks and birth weight was 959.2 ± 229.8 g. Hyperalimentation with lipid infusion was used in all cases. All of the neonates survived with antifungal agent use. IMPLICATIONS FOR PRACTICE: This study highlights that prophylactic fluconazole may be an associated factor of Malassezia colonization; M furfur remains a potential concern for fungemia in the care of premature infants and thus requires our attention. IMPLICATIONS FOR RESEARCH: Future studies should further investigate the incidence and impact of noncandidal fungal infections with fluconazole prophylaxis use in premature infants.